Lower-limb coordination adaptations to shooting distance in basketball: an exploratory angular velocity-based vector coding study - Feng, Ziyang; Xie, Zhonghao; Huang, Zhiguan; Huang, Wenwei; Mi, Xue; Li, Guoxing (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveThis exploratory study aimed to investigate how shooting distance is associated with the adaptations in lower limb inter-joint coordination of male university basketball athletes during the Loading and Jump Phases.MethodsKinematic data from 14 university basketball athletes performing jump shots at four distances (4.6 m, 5.8 m, 7.0 m, and 8.325 m) were collected using OpenCap. Inter-joint coordination was quantified using a vector coding technique based on angular velocity data. This approach was selected to conform with biomechanical conventions for calculating angular dynamics, preserve more temporal information, and make the measure more robust to any noise that may be present in the data. Subsequently, the adaptations were analyzed using Bayesian circular mixed-effects models.ResultsAnalysis of the data showed a primary adaptation in the Jump Phase: as shooting distance increased, coordination showed a trend towards greater Distal (knee and ankle) Dominancy. This change was underpinned by interaction effects (95% HPD that did not contain zero) between shooting distance and movement phase in multiple lower-limb joint couplings. Alongside this primary adaptation, an asymmetrical adjustment in the bilateral Knee-Ankle coordination during the Loading Phase emerged: with increasing distance, the right side showed enhanced Distal Dominancy while the left side trended towards Proximal Dominancy.ConclusionBased on these observed patterns, we propose two hypotheses for future confirmatory research: (1) that this trend towards greater Distal Dominancy may reflect a functional optimization of the lower limb for long-range shooting, and (2) that the observed asymmetry might be a functional adaptation to the specific demands of the shooting motion.